Predicting the Need for a Tier II Ototoxicity Study From Early Renal Function Data. (July 2019) - Gauvin, David V.; Zimmermann, Zachary J.; Yoder, Joshua; Tapp, Rachel; Baird, Theodore J.
History has established that many drugs, such as the antibiotics, chemotherapies, and loop diuretics, are capable of inducing both nephrotoxicity and ototoxicity. The exact mechanisms by which cellular damage occurs remain to be fully elucidated. Monitoring the indices of renal function conducted in the Food and Drug Administration's prescribed set of early investigational new drug (IND)–enabling studies may be the first signs of ototoxicity properties of the new drug candidate. In developing improved and efficacious new molecular entities, it is critically necessary to understand the cellular and molecular mechanisms underlying the potential ototoxic effects as early in the drug development program as possible. Elucidation of these mechanisms will facilitate the development of safe and effective clinical approaches for the prevention and amelioration of drug-induced ototoxicity prior to the first dose in man. Biomarkers for nephrotoxicity in early tier I or tier II nonclinical IND-enabling studies should raise an inquiry as to the need to conduct a full auditory function assay early in the game to clear the pipeline with a safer candidate that has a higher probability of continued therapeutic compliance once approved for distribution.